The socio-political context and the poetic talent: A study in Auden's poetry - Alrazzaq, Maytham Abed; Harb Mkhailef, Abbas, Mishaal (Opción, 2020)
This paper tends to highlight the political context of the poetry that is produced by W.H. Auden, as the poet who was active during the earlier twentieth century via comparative qualitative research methods. As a result, the poetry of W.H. Auden has represented the class differentiation, effects of war, depression, and the bleakness of the political disorder in Europe. In conclusion, the war images, exploitation and class distinction are vivid and honest witnesses to modernism and its degradation.